Pemodelan dan Visualisasi Rumah Tipe 45 Menggunakan Software Building Information Modelling - Gunawan, Gunawan; Gawei, Apria Brita Pandohop (Jurnal Basement : Jurnal Teknik Sipil, 2025)
The demand for residential housing in the city of Kota Palangka Raya continues to increase. Which is marked by the application for housing credit and the growing population. Therefore, the construction of residential houses needs to be done to meet these needs. This study aims to examine the efficiency of the application of Building Information Modeling (BIM) in modeling and visualization in house construction projects at CV. Katiga rancang putera which still uses conventional methods in its modeling.  The focus of this research is to improve design efficiency and reduce errors in calculations, such as material classification, area, and size, using Archicad software from Graphisoft. The research was conducted for 5 months November 2024-February 2025 at Jl. Untung Suropati, Kota Palangka Raya, with data in the form of Detail Engineering Design (DED). Analysis techniques included image conversion to DWG format, structural and architectural modeling, and visualization using Enscape. The results show that the application of BIM accelerates the 2D to 3D modeling process, improves design efficiency, and produces more realistic visualizations. In addition, this method facilitates error correction during the planning process, so it can support the construction of more accurate and quality residential houses in Kota Palangka Raya City